Synthesis of New Polyester-Amides from Polyvinyl Alcohol and Convert Some of Them to Polyester-Imide - Ahamed, Luma S (Al-Nahrain Journal of Science, 2011)
New fifteen polymers were prepared by modification of polyvinyl alcohol; these polymers were prepared by two steps. The first step was included reaction 1 mole of poly vinyl alcohol with 1mole of adipoyl chloride to produce ester-acid chloride polymer .Second step was included reaction the produced polymer in step one with different amines to obtained new ester-amide polymers .Four of them were reacted with acid chloride (acetyl chloride and benzoyl chloride) in DMF to produces ester imide polymers in third step. All these polymers have different physical properties which may be used in different applications. The prepared polymers were characterized by FTIR, 1HNMR spectroscopy, and by measuring their melting points, softing points, solubilities.